2016
DOI: 10.1039/c5fo01621e
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, morphological and cellular uptake properties of lutein nanodispersions prepared by using surfactants with different stabilizing mechanisms

Abstract: In this study, we prepared a series of lutein nanodispersions via the solvent displacement method, by using surfactants with different stabilizing mechanisms. The surfactants used include Tween 80 (steric stabilization), sodium dodecyl sulfate (SDS; electrostatic stabilization), sodium caseinate (electrosteric stabilization) and SDS-Tween 80 (electrostatic-steric stabilization). We then characterized the resulting lutein nanodispersions in terms of their particle size, particle size distribution, zeta potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In this study, Tween 20-stabilized emulsions showed a significantly lower astaxanthin cellular uptake than that of emulsions stabilized by whey proteins, lecithin, and their combinations. Similarly, Tan et al [43] reported that the cellular uptake of the lutein nanodispersion stabilized by sodium caseinate was higher than that which was stabilized by Tween 80. Thus, the type and nature of the emulsifiers may be a possible factor accounting for the cellular uptake efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Tween 20-stabilized emulsions showed a significantly lower astaxanthin cellular uptake than that of emulsions stabilized by whey proteins, lecithin, and their combinations. Similarly, Tan et al [43] reported that the cellular uptake of the lutein nanodispersion stabilized by sodium caseinate was higher than that which was stabilized by Tween 80. Thus, the type and nature of the emulsifiers may be a possible factor accounting for the cellular uptake efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…For the study, zeta potential was not analyzed due to the nonionic emulsifiers used. Hence, it would not contribute charges to the emulsion; instead, it will stabilize the emulsion by steric stabilization as described in Tan et al ().…”
Section: Resultsmentioning
confidence: 99%
“…As in any colloidal suspension, lipomers can undergo destabilization processes, such as Ostwald ripening. This process can be avoided by steric stabilization using Tween 80 [30]. Due to its HLB (14.9), Tween 80 acts as a stabilizer of the aqueous phase, coating the surfaces of the LPNCs and preventing their aggregation.…”
Section: Screening Of Experimental Variables On Nanoparticle Propertiesmentioning
confidence: 99%